Profile of lecturer competence in teaching Listening Comprehension - Arisman, Rizal; Supardi, La Ode (D3 English Program Universitas Merdeka Malang, 2019)
Lecturer competence becomes one of the factors influencing the success of learning. This research aims at investigating the lecturer competence in teaching Listening Comprehension subject at English Language Education Program of Dayanu Ikhsanuddin University. The design of this research uses a quantitative approach by applying a survey method. The population is fourth semester students and the sample is 60 students selected using simple random sampling technique. In collecting the data, this research uses a questionnaire from lecturer certification program which has 28 items, consists of 9 items for pedagogic competence, 8 items for professional competence, 6 items for personality competence, and 5 items for social competence. The result of this research indicates that the lecturerâ€™s pedagogic competence is in high category, professional competence is in high category, personality competence is in very high category, and social competence is in very high category. The most dominant lecturer competence in teaching Listening Comprehension subject is pedagogic competence since it is selected by 61.67% students.Â DOI:10.26905/enjourme.v4i2.3609